Implementation of the Bali Governor Regulation on the Restriction of Single-Use Plastic Waste Generation in the Environment of the Bali Provincial Government - I Putu Nanda Kusuma Adnyana (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This paper aims to understand the implementation of Bali Governor Regulation No. 97 of 2018 concerning the limitation of single-use plastic waste within the Bali Provincial Government. This qualitative, descriptive study uses in-depth interviews, field observation, and document analysis for data collection. The results show that the implementation of Bali Governor Regulation No. 97 of 2018 is not yet optimal within the Bali Provincial Government. There are several challenges in its execution, including: Many employees are still not aware of the need to bring their own water bottles. Bottled drinking water in glass bottles is limited and relatively expensive, so plastic bottled water remains the primary choice. A solution is to not only limit the circulation of bottled water under 1 liter as stated in Bali Governor Circular Letter No. 9 of 2025 on the Bali Clean Waste Movement but also to set a real example. This involves changing the material of bottled water from plastic to more easily degradable paper or cardboard.